MOG antibody seropositivity in a patient with encephalitis: beyond the classical syndrome - Mariotto, Sara; Monaco, Salvatore; Peschl, Patrick; Coledan, Ilaria; Mazzi, Romualdo; Höftberger, Romana; Reindl, Markus; Ferrari, Sergio (BMC neurology, 2017)
Background The presence of circulating anti-myelin oligodendrocyte glycoprotein antibodies (MOG-Abs) has been described in sera of patients with different inflammatory conditions of the central nervous system. In adults the core clinical feature is usually characterised by acute myelitis and/or optic neuritis. We here report an atypical case with serum and cerebrospinal fluid MOG-Abs and a clinical picture suggestive for acute encephalitis. Case presentation A 31-year-old Indian man presented with altered mental status, slight fever, and ataxia. Brain magnetic resonance imaging noted a widespread involvement of the white matter associated with slight cortical and subcortical damage in absence of contrast enhancement. An extensive infectious screening resulted negative while autoimmune analysis revealed the presence of MOG-Abs, detected with live cell-based assay. After treatment with intravenous immunoglobulins a marked and prompt clinical and radiological improvement was observed. Conclusions To date, several areas of uncertainty still remain regarding clinical features and prognosis of subjects with MOG-Abs. The description of atypical cases is crucial, since recognition of this condition leads to prompt treatment and better prognosis, as in the case here reported.